Deferred Surgical Treatment of Upper Limb Trauma in a Pandemic Context - Telo Ramos, Nuno (2024)
Introduction: In order to manage the high number of patients with upper limb fractures that require surgical treat‐ ment, it is essential to have a well‐defined structure, in order to promote an adequate response to each type of orthope‐ dic pathology and to fit the reality of all other pathologies. In order to reduce hospital stays and promote better treat‐ ment of patients, our service promoted the deferred treatment of numerous pathologies in the area of traumatology. The aim of the study was to assess the type of pathologies, patient characteristics, degree of satisfaction and pain con‐ trol of patients with upper limb fractures, treated in a deferred manner in our hospital, in 2020, a severely marked year by the global pandemic context by COVID‐19. Methods: We developed a retrospective observational study with the evaluation of 71 patients treated in a deferred manner and who waited at their home for a call for surgical treatment. Results: We recorded an average age of 49 years (14‐71), with 40 males (56.3%). The most frequent diagnoses were distal radius fracture (36.6%; n=26), metacarpal fracture (19.7%, n=14) and phalangeal fractures (11.3%, n=8). The average time from coming to the emergency department until definitive surgical treatment was 7 days and the most frequent anesthetic risk was ASA 2 (in 64.6%). After a telephone call made in May 2021, it was possible to assess 36 of the 65 patients operated, with 89% reporting satisfaction with the possibility of waiting for surgical treatment at home and 92% reporting recommending this type of strategy. About pain control at home, while waiting for surgery, applying the VAS score: the mean was 1.94 (0 – 9). We applied the score (QuickDASH) to all patients with distal radius fractures included in the group, with a mean of 18.2 points (0 – 65.9; SD 18.65). Conclusion: Deferred treatment of upper limb traumatic pathology was satisfactory for patients, who recommended the treatment and allowed pain control throughout the clinical course.